1995
DOI: 10.1007/s001250050351
|View full text |Cite
|
Sign up to set email alerts
|

Hyperresponse in calcium-induced insulin release from electrically permeabilized pancreatic islets of diabetic GK rats and its defective augmentation by glucose

Abstract: In spontaneously diabetic GK rats, insulin secretion from pancreatic beta cells in response to glucose is selectively impaired, probably due to deficient intracellular metabolism of glucose and impaired closure of KATP channels during glucose stimulation. By using electrically permeabilized islets of GK rats, we explored the functional modulations in exocytotic steps distal to the rise in [Ca2+]i in the diabetic condition. At 30 nmol/l Ca2+ (basal conditions) insulin release was similar between GK and non-diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 51 publications
(49 reference statements)
3
18
0
Order By: Relevance
“…These results have the potential to elucidate how SNARE proteins may not only regulate physiological insulin exocytosis but also be of pathophysiological significance in the dysregulation of Ca 2ϩ influx-mediated islet ␤-cell injury in diabetes (1)(2)(3). In fact, SNARE protein expression levels were diminished in islets of type 2 diabetic models, including Zucker fa/fa and GK rats (34,35), which exhibit abnormal regulation of Ca 2ϩ influx and insulin exocytosis (36). Reconstitution of these SNARE proteins, particularly SNAP-25 and syntaxin, partially restored insulin secretion to normal levels (35), likely by restoring the diabetic dysregulation of the distal components of the insulin exocytotic machinery, in particular the L C excitosome.…”
Section: Discussionmentioning
confidence: 98%
“…These results have the potential to elucidate how SNARE proteins may not only regulate physiological insulin exocytosis but also be of pathophysiological significance in the dysregulation of Ca 2ϩ influx-mediated islet ␤-cell injury in diabetes (1)(2)(3). In fact, SNARE protein expression levels were diminished in islets of type 2 diabetic models, including Zucker fa/fa and GK rats (34,35), which exhibit abnormal regulation of Ca 2ϩ influx and insulin exocytosis (36). Reconstitution of these SNARE proteins, particularly SNAP-25 and syntaxin, partially restored insulin secretion to normal levels (35), likely by restoring the diabetic dysregulation of the distal components of the insulin exocytotic machinery, in particular the L C excitosome.…”
Section: Discussionmentioning
confidence: 98%
“…Involvement of ion channels in this process is widely accepted and an increase in intracellular Ca 2+ levels is necessary to trigger exocytosis and release of insulin [68,76]. Furthermore, in isolated pancreatic islets of diabetic rats, impairment of insulin secretion is due to the inability of glucose to eventually increase the intracellular Ca 2+ concentration and trigger exocytosis [48,49]. The localization of TRPV5 suggests that it may play a role in the regulation of intracellular Ca 2+ homeostasis and insulin secretion.…”
Section: Pancreasmentioning
confidence: 98%
“…Desensitization of the K ATP channel to ATP has been reported (Tsuura et al, 1994), but is not believed to be a major cause of reduced insulin secretion. Indeed, studies have shown a hyperresponsiveness to Ca 2+ in Goto-Kakizaki rat electropermeabilized β cells (Katayama et al, 1995;Okamoto et al, 1995), which may represent a compensatory adaptation to decreased ATP production.…”
Section: Goto Kakizaki Ratsmentioning
confidence: 99%